USE OF BRADEN SCALE -A NARRATIVE REVIEW - Rekha Pant; Mannu; Diksha Biswal; Sadhana Rawat (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The main organ that covers our outside of the body is the skin. Skin is the largest organ in our body. One-third of the blood that the body circulates passes through it. The skin serves as a barrier against heat, light, chemicals, and physical exertion. The skin offers us the ability to feel touch, heat, and cold, shields us from viruses and environmental variables, and helps control body temperature. To fight infection, it actively works with the immune system. In addition to small scrapes, cuts, tears, blisters, or burns, destruction or skin breakdown can involve tissue degeneration that extends all the way to the bone. Anemia, malnutrition, and diabetes are some of the primary risk factors that might result in pressure ulcers either individually or in combination. Skin often serves as an indicator of our general wellness; healthy skin makes you feel good and makes you look nice. Good personal hygiene, an unpolluted environment, avoiding chemical contact, healthy eating practices, adequate relaxation, are all necessary for maintaining beautiful, healthy skinAim-This literature review aimed to check knowledge of Staff Nurses and Nursing students regarding prevention, cause &          treatment of pressure ulcers and use of Braden Scale.Method–An extensive search and numerous evaluation of the peer-reviewed literature was conducted for narrative review. Journal article were retrieved from three database (Pub Med, Medline, Embase & Research gate) using the search terms ‘pressure ulcer’ and ‘Braden Scale’.Result-The search yielded eleven studies related to knowledge among Staff Nurses regarding use of Braden Scale. Subsequent review identified people have very less knowledge regarding pressure ulcers and its occurrence.